A theory of the boundaries of banks with implications for financial integration and regulation - Falko Fecht; Roman Inderst; Sebastian Pfeil (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
We offer a theory of the "boundary of the firm" that is tailored to banking, as it builds on a single inefficiency arising from risk-shifting and as it takes into account both interbank lending as an alternative to integration and the role of possibly insured deposit funding. Amongst others, it explains both why deeper economic integration should cause also greater financial integration through both bank mergers and interbank lending, albeit this typically remains inefficiently incomplete, and why economic disintegration (or "desychronization"), as currently witnessed in the European Union, should cause less interbank exposure. It also suggests that recent policy measures such as the preferential treatment of retail deposits, the extension of deposit insurance, or penalties on "connectedness" could all lead to substantial welfare losses.
urn:nbn:de:hebis:30:3-374792
Keywords: 330